International criminal court : policy, status and overview policy, status and overview - Milton, Harry P. (New York : Nova Science, 2009)
Excerpted from CRS reports.--Preface.
Excerpted from CRS reports.
Includes bibliographical references and index.
Keywords: International Criminal Court; International criminal courts; Cour pénale internationale